Inequality and Growth: The Role of Beliefs and Culture - Martin Strieborny (Lund University, School of Economics and Management, Department of Economics, 2013)
Governments perpetually align their policies to satisfy shifts in voters' relative demand for economic growth versus social equality. Following such shifts, increases (decreases) in government interventions lower (raise) both inequality and growth. This mechanism generates a positive co-movement between inequality and growth. The pattern is weaker in countries where a culturally determined belief that the rich are deserving renders equality a less important objective in the first place. I develop this analytical result in the theoretical framework of Alesina and Angeletos (2005), and I provide robust empirical support for it in a panel of 38 countries over the period 1964-2004.
Keywords: O15; O40; P16; Z10; 330; culture; inequality; growth